Model Perlindungan Hukum bagi Masyarakat Pelanggan PT. PLN (Persero) sebagai Konsumen atas Pelaksanaan Penertiban Pemakaian Tenaga Listrik (P2TL) di Kabupaten Jember, Bondowoso dan Situbondo - Dodik Prihatin A.N; Samsudi Samsudi (JURNAL RECHTENS, 2016)
Customer satisfaction is a situation where desires, hopes, and customer needs can be met. A service is considered satisfactory if the service can meet the needs and expectations of customers. Customer satisfaction measurement is an important element in providing better services, more efficient, and more effective. Institutionally, PLN has been providing services based on professionalism. On the other hand, one of the contributors to high losses (loss of power) is a dishonest act committed by some electricity consumers who have no good intentions towards the use of electricity. Therefore, in order to reduce losses from the non-technical factors, PLN issued a policy such as Power Consumption Control program called P2TL. Program P2TL by PT. PLN is done they often lead to friction, it is very possible because of lack of socialization and also the level of consumer understanding of the regulations or policies of the PLN, so do also the socialization of the importance of Controlling Power Consumption (P2TL) and legal protection solutions.